Loss of epithelial Gq and G11 signaling inhibits TGFβ production but promotes IL-33–mediated macrophage polarization and emphysema - John, Alison, E.; Wilson, Michael, R.; Habgood, Anthony; Porte, Joanne; Tatler, Amanda L.; Stavrou, Anastasios; Miele, Gino; Jolly, Lisa; Knox, Alan J.; Takata, Masao; Offermanns, Stefan; Jenkins, R. Gisli (American Association for the Advancement of Science, 2016)
Heterotrimeric guanine nucleotide–binding protein (G protein) signaling is a ubiquitous signaling system that links hundreds of G protein–coupled receptors (GPCRs) with four G protein signaling pathways. Two of these pathways, one mediated by Gq and G11 and the other by G12 and G13, are implicated in the force-dependent activation of transforming growth factor–β (TGFβ) in lung epithelial cells. Reduced TGFβ activation in alveolar cells leads to emphysema, whereas enhanced TGFβ activation promotes acute lung injury, and idiopathic pulmonary fibrosis, therefore precise control of alveolar TGFβ activation is essential for alveolar homeostasis. Here, we investigated whether the Gq/G11 or G12/G13 pathways in epithelial cells are required to generate TGFβ and suppress alveolar inflammation. Mice deficient in both Gαq and Gα11 developed inflammation primarily due to alternatively activated (M2-polarized) macrophages, enhanced production of matrix metalloprotease 12 (MMP12), and age-related alveolar airspace enlargement consistent with emphysema. We found that mice with impaired Gq/G11 signaling had reduced stretch-mediated generation of TGFβ by epithelial cells and elevated macrophage MMP12 synthesis, but were protected from the effects of ventilator-induced lung injury. Furthermore, synthesis of the pleiotropic cytokine interleukin-33 (IL-33), was increased in these alveolar epithelial cells resulting in the M2-type polarization of alveolar macrophages independently of the effect on TGFβ. Our results suggest that alveolar Gq/G11 signaling maintains alveolar homeostasis and is likely to independently upregulate mechanotransduced epithelial TGFβ activation and downregulate epithelial IL-33 synthesis. Together, these findings suggest that disruption of Gq/G11 signaling promotes inflammatory emphysema, but protects against mechanostransduced lung injury.